Myopenia and body fat distribution in hospitalized ulcerative colitis patients: correlations with clinical characteristics and response to vedolizumab - Wei, Wei; Yan, Pengguang; Zhang, Yan; Wang, Qiong; Kang, Junren; Liu, Pengju; Fu, Jin; Li, Jingnan; Yu, Kang (Frontiers in Nutrition, 2024)
BackgroundUlcerative colitis (UC) patients often suffer from impaired nutritional conditions. However, there are few studies focused on muscle loss in UC patients as well as its impact on therapeutic response. This study aimed to investigate the prevalence of myopenia in hospitalized patients with active UC, analyze the relationship between body composition including both skeletal muscle and fat with clinical characteristics, and explore the association between body composition and clinical response to vedolizumab.MethodsA retrospective cohort study was conducted in hospitalized patients with active UC in Peking Union Medical College Hospital from November 2014 to October 2022. Computed tomography (CT) scans were used to measure skeletal muscle area, visceral fat area (VFA), subcutaneous fat area (SFA), and intramuscular fat infiltration at the third lumbar vertebrae (L3) level. These measurements were standardized by height (m) squared. Myopenia was defined as a skeletal muscle index (SMI) < 44.77 cm2/m2 for males and <32.50 cm2/m2 for females. The VFA/SFA ratio (VSR) served as an indicator of visceral obesity, while intramuscular fat infiltration was evaluated using the mean Hounsfield Unit (HU) value of the L3 skeletal muscle section.ResultsA total of 457 patients were enrolled. The prevalence of myopenia was 49.7% in this cohort. Female patients had significantly higher levels of subcutaneous fat and intramuscular fat but a lower level of visceral fat than male patients. SMI and mean HU showed positive correlations with serum albumin (ALB) and negative correlations with serum high-sensitivity C-reactive protein (hsCRP), whereas VSR showed the opposite trend. Among the 92 patients who received vedolizumab treatment, myopenia was significantly associated with a lower clinical response rate, and this association remained significant after adjusting for vedolizumab duration, ALB, and hsCRP (OR = 3.458, 95% CI 1.238–9.659, p = 0.018). Visceral obesity, defined as VSR ≥ 75th centile of gender-specific VSR, tended to diminish the clinical response rate but did not reach statistical significance.ConclusionThis study underscores the significance of assessing body composition in UC patients. Optimizing body composition should be considered an integral component of managing UC patients in the future.